(untitled) (FULafia Journal of Science and Technology, 2026)
Graph energy has increased tremendously, and many versions of the energy have been conceived and proposed. The products of connected graphs play a vital role in the study of DNA analysis. In this paper, the adjacency energy of the tensor product, strong product, Cartesian product, and categorial product of a complete graph ???????? and a cycle graph ????????, were computed. The products ????3⊗????4, ????3⊗????3,????4⊗????4,????3⊠????4,????4⊠????4,????3×????4,????3×????3,???????????? ????4×????4 were considered. The adjacency matrix and associated eigenvalues were computed, and the relationship between the graph energies was established.